A Comparative Study of the Performance of SrCo0.76Fe0.19Al0.1Ox and (SrCo0.8Fe0.2O3-deltda)0.95(SrAl2O4)0.05 Mixed-Conducting Membranes - Zhu, N.; Zhang, G.; Liu, Z.; Dong, X.; Jin, W.; Liu, Shaomin (Wiley-Blackwell Publishing, Inc., 2013)
Dense oxygen permeable ceramic membranes are promising materials for separating oxygen from air and for syngas production. The crystal structure, oxygen vacancy, microstructure, thermal expansion behavior, electrical conductivity, and oxygen permeability of two mixed-conducting ceramics: 5 mol% SrAl2O4-doped SrCo0.8Fe0.2O3-delta (SCF-SA) and SrCo0.76 Fe0.19Al0.1Ox (SCFA), with the same overall cation composition, were systematically investigated in this work. The main phases of SCFA and SCF-SA are cubic perovskite and no orthorhombic brown millerite appears from 700°C to 900°C in air, while SCF-SA presents minor unidentified phases. SCF-SA shows lower electrical conductivity than SCFA. SCFA membranes exhibit lower oxygen permeation flux than SCF-SA. At 850°C, the oxygen permeation fluxes of SCFA and SCF-SA are 1.23 and 1.46 mL/cm2/min, respectively, under the oxygen partial pressure gradient of 0.21 x 10^5/1 3 10^2 Pa.